Darboux Rotation Axis of Spacelike Biharmonic Helices with Timelike Normal in the Lorentzian E(1, 1) - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study Darboux rotation axis for spacelike biharmonic helices in the Lorentzian group of rigid motions E(1, 1). We obtain equation of Darboux vector of spacelike biharmonic helices in the Lorentzian E(1, 1).
Keywords: Rigid motion; Darboux rotation; Bienergy